L’animal-machine. Élevage industriel et biotechnologies - Catherine Larrère (Cahiers d’histoire.)
Introduced by Descartes, the metaphor of the animal-machine has largely survived him and his philosophy. This is because it is a technical model, which does not say what animals are (everyone knows that they are not machines) but how they should be considered (it is a heuristic model) if certain results are to be obtained (it is a prescriptive model). It has therefore been used all the more as the instrumentalisation of farm animals for productivist purposes increased from the 19th to the 21st century. Using the reference to the animal-machine as a guideline, we follow the stages of the technical control of animals, from the zootechnics of the 19th and 20th centuries (the animal as a production machine) to the ambitions of biotechnology in the 21st century (the manufacture of the animal). This type of treatment of animals, which is a way of denying them their reality as living, sentient beings, has continually provoked an ethical criticism that aims at other relationships between humans and animals.